Content Analysis and Development Design for Digital Magazine - Veselá, Anna (2020)
The aim of this Master’s Thesis is to determine satisfaction with the content of the digital magazine BezHladovění.cz and to reveal possible complications that hinder the reading experience. The author focuses on individual articles, illustrative images and video content. The primary research group of respondents are readers of BezHladovění.cz and the secondary group is represented by people interested in a healthy lifestyle. The Design Thinking method was used for the best possible understanding of problems and unheard wishes of the research sample. This method served as an extension of mixed research consisting of a questionnaire survey and in-depth interviews. Based on the obtained data, recommendations were prepared for the editors of BezHladovění.cz magazine, which represent possible solutions to the problem and the unsatisfied wishes of readers. Respondents identified the breakdown and inconsistency of content as the most serious problems. The development proposals are primarily intended for the digital magazine BezHladovění.cz, but they can also be useful for administrators of other internet platforms.